Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3233/jad-170163
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibrillary Tangles of Aβx-40 in Alzheimer’s Disease Brains

Abstract: Abstract. The two pathognomonic lesions in the brain of AD patients are senile plaques and intraneuronal neurofibrillary tangles (NFT). Previous studies have demonstrated that amyloid-␤ (A␤) is a component of both senile plaques and NFTs, and have showed that intracellular accumulation of A␤ is toxic for cells and precedes the appearance of extracellular amyloid deposits. Here we report that there are numerous intraneuronal NFT and extraneuronal NFT immunoreactive for A␤ x-40 in which there is no co-localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
(81 reference statements)
2
13
0
Order By: Relevance
“…More and more evidence demonstrates that iAβ is responsible for early synaptic dysfunction and neuronal loss, plaque formation and cognitive impairment; in other words, iAβ is the toxic Aβ species [128]. It was demonstrated by immunochemistry that iAβ is able to form NFTs [132]. Accumulation of iAβ precedes tau hyperphosphorylation and is associated with microtubular degeneration.…”
Section: Intracellular Aβ and Extracellular Plaquesmentioning
confidence: 99%
“…More and more evidence demonstrates that iAβ is responsible for early synaptic dysfunction and neuronal loss, plaque formation and cognitive impairment; in other words, iAβ is the toxic Aβ species [128]. It was demonstrated by immunochemistry that iAβ is able to form NFTs [132]. Accumulation of iAβ precedes tau hyperphosphorylation and is associated with microtubular degeneration.…”
Section: Intracellular Aβ and Extracellular Plaquesmentioning
confidence: 99%
“…In addition, Aβ 40 is the main component of amyloid deposition occurring in cerebral amyloid angiopathy (CAA) [ 14 ], which has a prevalence of about 80–90% in patients with AD [ 15 ]. In keeping with this, previous studies have demonstrated that specific anti-Aβ 40 antibodies label intra- and extra-neuronal NFTs in the entorhinal cortex and the hippocampus of AD brains, and that these do not co-localise with tau NFTs, suggesting the presence of degenerating neuronal populations filled with C-terminal fragments of Aβ x-40 [ 16 ].…”
Section: Introductionmentioning
confidence: 53%
“…Although Aβ 42 is regarded as the most toxic species, other studies have shown that Aβ 40 can also form cytotoxic aggregates [ 9 , 53 , 54 ]. Additionally, it has been observed that the levels of insoluble Aβ 40 in the brain of patients with AD increase substantially in association with the onset of dementia [ 11 , 12 ], and we have found large numbers of degenerating neurons filled with C-terminal fragments of Aβ x-40 (but not Aβ x-42 ) in the entorhinal cortex of AD brains [ 16 ]. These results support the idea that Aβ 40 could play a relevant role in the pathophysiology of AD.…”
Section: Discussionmentioning
confidence: 85%
“…The above-mentioned pathological aggregates constitute the primary biomarkers for AD diagnosis [24]. Senile plaques are mainly composed of the pathological form of Aβ, whereas the major component of NFTs is the hyperphosphorylated form of tau protein [25,26]. Numerous hypotheses regarding the AD etiology have been presented, but the AD pathogenesis still remains not fully understood [27].…”
Section: Alzheimer's Diseasementioning
confidence: 99%